2021
DOI: 10.2196/26559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Usage of COVID Coach, a Public Mental Health App Designed for the COVID-19 Pandemic: Evaluation of Analytics Data

Abstract: Background The COVID-19 pandemic has significantly impacted mental health and well-being. Mobile mental health apps can be scalable and useful tools in large-scale disaster responses and are particularly promising for reaching vulnerable populations. COVID Coach is a free, evidence-informed mobile app designed specifically to provide tools and resources for addressing COVID-19–related stress. Objective The purpose of this study was to characterize the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
(44 reference statements)
6
29
1
Order By: Relevance
“…Actual data on app engagement from over 100,000 participants in different studies across various health conditions showed that the median participant retention was just 5.5 days 203 . As mentioned before, this dropoff in use was also found in a 2021 report of the stress app COVID Coach, which reported that only 1.56% of users remained engaged for at least 14 days 115 . Research data also do not confirm commonly held assumptions that older adults will engage less than younger people 203 , although other reviews suggest the opposite 197 .…”
Section: Recipients Of Innovation: Patient Factorssupporting
confidence: 71%
See 1 more Smart Citation
“…Actual data on app engagement from over 100,000 participants in different studies across various health conditions showed that the median participant retention was just 5.5 days 203 . As mentioned before, this dropoff in use was also found in a 2021 report of the stress app COVID Coach, which reported that only 1.56% of users remained engaged for at least 14 days 115 . Research data also do not confirm commonly held assumptions that older adults will engage less than younger people 203 , although other reviews suggest the opposite 197 .…”
Section: Recipients Of Innovation: Patient Factorssupporting
confidence: 71%
“…While commercial app companies do not publish engagement data, it is clear that downloads do not automatically translate into active use. For example, the popular (and free) COVID Coach app designed to address stress during the pandemic re ported over 140,000 downloads, but only 1.56% of individuals who have downloaded the app recorded at least two weeks of use 115 .…”
Section: Self-management Of Depression and Anxietymentioning
confidence: 99%
“…For alcohol, 30.35% of our sample were identified with risky use of alcohol, which is higher than what was found (8.6% to 23.6%) in a general population study aged 18-75 years (34). Thus, it is possible that the application was more appealing for at-risk individuals (22). Current tobacco users were more frequently identified as being at risk of an SUD diagnosis (around 70% with CDS-5) than alcohol users (around 33% with CAGE), and they were more likely to report a problem of use since the context of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use diary was helpful for almost half of the users but used by a minority only. Low ongoing use has been found in other populations using a mental health application during COVID (22). In general, the use of mental health applications is waning over time, and a small proportion of users actually use popular applications regularly (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation